2017
DOI: 10.1183/13993003.01885-2015
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of patients with uncontrolled asthma: clinical features of asthma patients according to the level of control achieved (the COAS study)

Abstract: Our aim was to study the asthma control achieved in patients with uncontrolled asthma who had received appropriate treatment according to the Global Initiative for Asthma (GINA) 2010 (valid at the time the study was designed), and to analyse the factors associated with a lack of asthma control.This was a multicentre study in routine clinical practice performed in patients with uncontrolled asthma according to GINA 2010. At visit 1, we recorded demographics, asthma characteristics and spirometry. We assessed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 39 publications
0
21
0
1
Order By: Relevance
“…Current GINA report recommends objective lung function measurements as necessary for initial diagnosis of asthma as well as long-term monitoring of asthma 1 . Previous studies have shown that reliance on patient-reported clinical symptoms [38][39][40][41] or ACT score can lead to overestimation of asthma control 41,42 . Inclusion of spirometry in the assessment guarantees more accurate monitoring of asthma control [38][39][40][41] without input from secondary care 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Current GINA report recommends objective lung function measurements as necessary for initial diagnosis of asthma as well as long-term monitoring of asthma 1 . Previous studies have shown that reliance on patient-reported clinical symptoms [38][39][40][41] or ACT score can lead to overestimation of asthma control 41,42 . Inclusion of spirometry in the assessment guarantees more accurate monitoring of asthma control [38][39][40][41] without input from secondary care 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The determinants which may contribute to inadequate asthma control include obesity, smoking and nonadherence to treatment [2,8,21]. Also incorrect use of inhaler devices and poor inhaling techniques are possible reasons leading to worsening of the asthma control [12]. It is commonly known that adherence to ICS treatment is unsatisfactory affecting management of asthma [11,28].…”
Section: Discussionmentioning
confidence: 99%
“…While assessing controller treatment and possible changes to ICS therapy the disease control, responsiveness to treatment and future risks must be taken into account for finding the appropriate step-up or step-down phases in treatment [2,15]. A previous study examined the effects of step-up treatment to uncontrolled adult asthma patients and showed that in spite of the optimization of the treatment most patients continued to show inadequately controlled asthma [12]. In our study patients with uncontrolled asthma had significantly more ICS dose changes and increases in ICS dose than patients with controlled asthma during 12-year follow-up period suggesting that physicians have tried to improve the management of asthma by changing the ICS dose of uncontrolled patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations